1986
DOI: 10.1002/chin.198611322
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: (Tertiary Phosphine) Gold(I) Derivatives of 2‐Pyridones.

Abstract: Die Herstellung der 2‐Pyridongoldphosphin‐Komplexe (III) aus den entsprechenden Pyridonen (I) und den Phosphingoldchloriden (II) wird beschrieben und die Struktur der Komplexe anhand der Röntgenstrukturanalyse von (IIIe) untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 1 publication
5
52
0
Order By: Relevance
“…These data confirmed that in several cases molecules of solvents can be clathrated in the solids, a frequent observation in the chemistry of the heterocyclic derivatives of gold e.g. : l-(triphenylphosphinegold)-6-methyl-2-pyridone [7] or l-tri(cyc/o-hexyl)phosphinegold-2-/so-propylimidazole [8]. The ligand L is triphenylphosphine for several reasons: the starting compound LAuCl is easily obtained and handled, the corresponding products are generally soluble in organic solvents, and the A u -P bond is not as easily broken as, for example, the A u -As or the A u -Sb bond of similar compounds having triphenylarsine or triphenylstibine in the place of L [8,11].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…These data confirmed that in several cases molecules of solvents can be clathrated in the solids, a frequent observation in the chemistry of the heterocyclic derivatives of gold e.g. : l-(triphenylphosphinegold)-6-methyl-2-pyridone [7] or l-tri(cyc/o-hexyl)phosphinegold-2-/so-propylimidazole [8]. The ligand L is triphenylphosphine for several reasons: the starting compound LAuCl is easily obtained and handled, the corresponding products are generally soluble in organic solvents, and the A u -P bond is not as easily broken as, for example, the A u -As or the A u -Sb bond of similar compounds having triphenylarsine or triphenylstibine in the place of L [8,11].…”
Section: Resultssupporting
confidence: 78%
“…Our investigations in the field of gold chemistry have been concerned with the interaction between Au(I) and several nitrogen-containing heterocycles such as pyrazoles [3], pyrazolones [4], indazoles, imidazoles [5], triazoles, tetrazole [6], or pyridones [7]. Isolation and characterization of several N-and of a few C-(trisubstituted phosphine)gold(I) deriva tives of the said molecules was reported.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Applications of the isonitrile and NAC gold complexes in the field of luminiscent compounds, [12] laser-induced writing with gold on ceramic surfaces, [13] liquid crystals [14] and water-soluble complexes [14] have been reported. The first NHC complex of gold(I) was prepared in 1989, [15] and at present these gold carbene complexes are the dominating car- …”
Section: Introductionmentioning
confidence: 99%
“…NHCÀGold(I) complexes have been known since 1989, and they can be neutral or cationic, with the respective formulas (NHC)AuX and [(NHC) 2 Au]X [33]. They are now widely used as catalysts for organic transformations such as nucleophilic additions on alkynes [34].…”
mentioning
confidence: 99%